Um olhar sobre a interculturalidade no livro didático de espanhol: os gêneros como mediadores culturais - Guadelupe, Lucila Carneiro (2014)
The presen t study, which is situated in the Linguistics area - Linguistics and Language Teaching, aims to verify whether the guidelines indicated in the official documents articulate with the intercultural proposals presented by the textbook . In general terms, throu gh an analysis of textbooks, we observed whether interculturality is present in the book and whether the work that has been done with discursive genres takes into consideration an intercultural perspective. We verified if a dialogue between cultures, the c ulture s of the target language and Brazilian culture s , exists considering not only the Peninsular Spanish, but also the presence of Hispanic - America in the teaching materials. We aimed to establish a correlation between the interculturality approach and th e proposals presented by official documents. In order to do that, the corpus analysis was done based on: genre theories, especially , Bakhtin's propositions (1979/2010; 1929/1995), and the concept of culture and interculturality by Aguilera Reija et al , (20 09). We also used as research sources official documents that view language teaching as culture. This study demonstrated that the discourse genres found in the textbook “ Enlaces: español para jóvenes brasileños”, more specifically in the section “ Más cosa s‖, portray representative subjects for the culture s of young people in terms of sociocultural experiences, and also allow a reflection on the construction of meanings in an interculturality perspective. The obtained results also confirmed that the proposa ls presented by the collection, in their majority, are consistent and make the intercultural function of genres clear, mainly, of those that effectively circulate in the social world. Concerning the impacts for future research, this study intends to supply subsidies for the (re)cognition of the importance that must be giv en to the intercultural perspective , considering, primarily, the didactic - pedagogical proposals presented by textbooks and their use in the classroom.